Sequence and regulation of European eel prolactin mRNA - Quérat, B.; Cardinaud, B.; Hardy, A.; Vidal, B; d'Angelo, Gisela (Molecular and Cellular Endocrinology, 1994)
International audience cDNA clones encoding the European eel (Anguilla anguilla L.) prolactin were isolated from a pituitary cDNA library constructed in gamma gt10, using a rainbow trout Prl cDNA fragment as a probe. Four different inserts were subcloned into the pGEM 3Z plasmid after PCR amplification. The 1082 bp-long nucleotide sequence revealed an open reading frame of 627 bp encoding a 24 amino acid-long signal peptide followed by a 185 amino acid-long mature protein. Comparison studies showed 60-70% homology with other known teleost fish prolactins and 30-45% with non-teleost fish, amphibian, reptilian, avian and mammalian prolactins. In situ hybridization studies using labelled prolactin RNA probe showed a strong signal in the rostral pars distalis of the pituitary gland. We next examined the physiological regulation of this prolactin synthesis in vivo using Northern blot analysis and prolactin cDNA probe labelled by random priming. The pituitary prolactin mRNA level was markedly decreased 3 weeks after transfer of eels from freshwater to sea water. Implants of thyroid hormones left for up to three weeks were ineffective on prolactin mRNA. Estradiol administered as implant, alone or in combination with 500 micrograms testosterone, was also unable to significantly alter the pituitary mRNA level for prolactin in the freshwater silver eels whatever the dose used (20-500 micrograms) and whatever the duration of treatment (from 4 days to 10 weeks).